2021
DOI: 10.1108/ijilt-01-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cognitive, social and teaching presences during emergency remote teaching at a South African university

Abstract: PurposeThis study aims to examine how lecturers at a South African university navigated teaching and learning in the current educational landscape obscured by the global pandemic. The authors examine how lecturers employed a community of inquiry (CoI) in their online classrooms within the context of emergency remote teaching (ERT). The study further aims to ascertain students’ feedback concerning current ERT practices at the university toward cultivating a CoI. Doing this would offer more appropriate intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(72 reference statements)
2
6
0
Order By: Relevance
“…They spend more time and effort studying the materials given by their respective teachers. It further confirms the study of Waghid, Meda, & Chiroma (2021) in South Africa, which underscores the vital role of teachers' presence in guiding students in establishing appropriate cognitive and social presence in an online community in the midst of the pandemic.…”
Section: Challenge C 2: Issues Of Equitysupporting
confidence: 78%
“…They spend more time and effort studying the materials given by their respective teachers. It further confirms the study of Waghid, Meda, & Chiroma (2021) in South Africa, which underscores the vital role of teachers' presence in guiding students in establishing appropriate cognitive and social presence in an online community in the midst of the pandemic.…”
Section: Challenge C 2: Issues Of Equitysupporting
confidence: 78%
“…Another study conducted in Egypt by Zalat, Hamed and Bolbol (2020) on the experiences of the academics during the COVID-19 pandemic reveals that synchronous (Zoom and Microsoft Teams) and asynchronous (recorded lectures, supportive videos, external links for recommended websites and electronic books) e-learning were used via a learning management system (LMS). Similarly, to the aforementioned study, Waghid, Meda and Chiroma (2021) found that lecturers in the Kenyan context used synchronous classes and asynchronous methods. The lecturers engaged students in discussions during synchronous classes using Zoom breakout rooms and Blackboard Collaborate .…”
Section: Zulusupporting
confidence: 57%
“…The findings of the aforementioned study reports that the instructor focused more on content and skills development, while to a certain extent overlooking the necessity to foster social presence (Carlon, 2020). Waghid, Meda and Chiroma (2021) have assessed cognitive, social and teaching presences during emergency remote learning at a South African university. These authors established that exposing students to all three presences give them opportunities to attain 21st-century skills that are essential graduate attributes.…”
Section: Zulumentioning
confidence: 99%
“…Given that engagement was a complex factor, it is suggested that administrators, teaching staff, and technical staff work together to propose strategies to engage students in blended and ERT modes. For example, following the CoI framework and inspired by Waghid et al ( 2021 ), course instructors can design interactive activities between students and teachers facilitating social presence, offer feedback for students’ self-reflection to enhance their cognitive presence, and give necessary explanations and guidance if required to strengthen teaching presence. Through establishing logic connections between teaching, social, and cognitive presence, students may perceive that learning in blended and ERT situations is well supported and justified, probably improving their engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Direction means that instructors “provide intellectual and scholarly leadership and share their subject matter knowledge with students” (Anderson et al, 2001 , p. 8). Waghid et al ( 2021 ) examined how lecturers established a CoI among their students within the context of ERT, finding that they focused on developing students’ cognitive capacities, while social presence was the least concerned. Regarding TP, there was a higher level of design than facilitation and direction.…”
Section: Literature Reviewmentioning
confidence: 99%